PENGARUH GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada Perusahaan-Perusahaan Properti dan Real Estate yang Go-Public di Bursa Efek Indonesia) - Intan Lifinda Ayuning Putri; Yeney Widya Prihatiningtyas (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study examined the effect of good corporate governance and ownership structure on the financial performance of a company. Good corporate governance was identified by the proportion of independent commissioner board, while ownership structure was proxied by the proportion of institutional and managerial ownership. The indicators of financial performance were measured by Return on Equity (ROE) and Return on Asset (ROA). The study used 22 companies as a sample from a population of 54 property and real estate companies listed on the Indonesian Stock Exchange and got total data 110 in the period 2008-2012. The sample was determined using purposive sampling method. The study used multiple regression analysis and the data were analysed using SPSS. Measured by ROE, the result showed that there was negative effect of the proportion of independent commissioner board and institutional ownership on firm financial performance. However, it was not found that managerial ownership had an influence on financial performance. Another result showed that the proportion of independent commissioner board, the proportion of institutional and managerial ownership had a positive effect on financial performance were measured by ROA.Keywords: good corporate governance, ownership structure, firm financial performance